2016
DOI: 10.1676/1559-4491-128.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Perch Usage by Hummingbirds in a Fragment of Atlantic Forest in Brazil

Abstract: Total de espécies de aves do Brasil (1981Brasil ( -2013 CBRO | LISTAS DAS AVES DO BRASIL | 11ª. Ed.2 Além do acúmulo de novidades ao longo de três anos, a lista nova espelha em seus números a quantidade crescente de trabalhos taxonômicos e sistemáticos na ornitologia, fruto em parte da sempre destacada revolução por que passa a Zoologia (e a biologia) com o desenvolvimento de técnicas de análise moleculares (cada vez mais acessíveis), mas também na disponibilidade cada vez maior de dados como gravações sonoras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although not explicitly tested in our study, use of auditory and visual signals for territory advertisement by hummingbirds could influence the relationship between location of core areas and canopy height (Ewald and Bransfield , Ornelas et al ). In addition, use of exposed perches by hummingbirds is often associated with detection of intruders, leading to a correlation between territorial movements and visibility (Rousseu et al , Lanna et al ). Further direct comparisons between the density of exposed perches and space‐use patterns in territorial hummingbirds are needed to test these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Although not explicitly tested in our study, use of auditory and visual signals for territory advertisement by hummingbirds could influence the relationship between location of core areas and canopy height (Ewald and Bransfield , Ornelas et al ). In addition, use of exposed perches by hummingbirds is often associated with detection of intruders, leading to a correlation between territorial movements and visibility (Rousseu et al , Lanna et al ). Further direct comparisons between the density of exposed perches and space‐use patterns in territorial hummingbirds are needed to test these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Natural perches are commonly utilized by hummingbirds for short rests while moving across the land, as well as for territorial defense. Recent research has suggested that some hummingbird species prefer perches less than 2 m in height and less than 4 mm in diameter (Lanna et al, 2016). The low richness and incidence of this family in the present review might be associated with the utilization of artificial perches outside the preferences of this group.…”
Section: Referencementioning
confidence: 60%
“…The artificial drinker contained three 200 ml (Mr. Pet®) artificial flowers and was filled with a 25% sugar solution. The fountain was remained available throughout the day, and the mixture was always replaced every morning (Lanna et al 2016, Lanna et al 2017).…”
Section: Methodsmentioning
confidence: 99%